2006
DOI: 10.1111/j.1346-8138.2006.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha‐hydroxy acids on the human skin of Japanese subjects: The rationale for chemical peeling

Abstract: Alpha-hydroxy acid (AHA) agents, such as glycolic acid and lactic acid, have been used as therapeutic agents for more than a quarter of a century. Recently, they have been used as agents to rejuvenate photo-aged skin. It is believed that these AHA agents induce the epidermis to remodel and accelerate desquamation, thus exerting their therapeutic effects. In this study, we investigated the histological differences in skin treated with glycolic, lactic, citric and acetic acids once daily for 6 weeks. The melanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 16 publications
1
56
0
2
Order By: Relevance
“…Yamamoto et al [3] found that treatment with glycolic acid can cause improvements in both the epidermal and dermal components and support the usefulness of AHA for rejuvenating photo-damaged skin. Furukawa and Yamamoto [13] revealed that glycolic acid of the appropriate pH increased the thickness of the treated skin and made the melanin pigments in the basal layer less prominent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamamoto et al [3] found that treatment with glycolic acid can cause improvements in both the epidermal and dermal components and support the usefulness of AHA for rejuvenating photo-damaged skin. Furukawa and Yamamoto [13] revealed that glycolic acid of the appropriate pH increased the thickness of the treated skin and made the melanin pigments in the basal layer less prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al [3] mentioned that GA in mix peeling had effects to increase the epidermal thickness, the hyaluronic acid, collagen I, procollagen I, and mucopolysaccharides, but to reduce the fragmentation of elastic fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3), implying that the effects of FDP might be caused by systemic changes in both the epidermis and dermis. These similar changes were observed in the process of chemical peeling, which destroys the epidermis and the dermis to regenerate new epidermis and dermis (19)(20)(21). The effects of these agents such as alpha hydroxy acids (AHAs), and lactic acid, have been proved to be mediated by the induction of epidermal remodelling, the acceleration of desquamation and the increase in collagen 1 in the upper dermis.…”
Section: Resultsmentioning
confidence: 64%
“…Glycolic acid (GLA) is used in the preparation of a large variety of products, including consumer and industrial cleaners, [1] personal care products, [2] and as a monomer in the preparation of polyglycolic acid (PGA) for dissolvable sutures, [3] drug-delivery materials [4] and gas barrier packaging materials. [5] The majority of glycolic acid currently produced commercially is prepared by the high-pressure, high-temperature reaction of formaldehyde and carbon monoxide by acid catalysis.…”
Section: Introductionmentioning
confidence: 99%